Prevalence of excess weight and associated socio-demographic factors among postmenopausal women: A population-based study in Ghana - Isaac Mensah Bonsu; Corlia Brandt; Adedayo T. Ajidahun; Monday O. Moses; Hellen Myezwa (AOSIS, 2023)
Background: Excess weight (obesity and overweight) is a pervasive condition that is considered a global epidemic and a threat to public health. Furthermore, numerous changes in fat deposits occur with the advent of menopause, leading to a change in the distribution of body fat. Knowledge of sociodemographic factors and prevalence can inform the effective management of these women. Aim: This study aimed to investigate the prevalence of excess weight among postmenopausal women in Ghana's Bono East (Techiman) region. Setting: This study was conducted in Bono East regional capital, Techiman, Ghana. Methods: This is a cross-sectional study conducted over 5 months at Bono East regional capital, Techiman in Ghana. Anthropometric parameters such as body mass index (BMI), waist-to-hip ratio (WHR) and waist-to-height ratio (WHtR) were obtained using physical measurements while socio-demographic data were gathered using questionnaires. Data analysis was performed using IBM SPSS 25. Results: The mean age of the 378 women who participated in the study was 60.09 ± 6.24 years. Body mass index, WHtR and WHR indicated excess weight of 73.2%, 91.8% and 91.0%, respectively. Education and ethnicity were predictors of excess weight (WHR). Women of the Ga tribe with high school education have 4.7- and 8.6-times increased odds of having excess weight. Conclusions: There are higher prevalence rates of excess weight (obesity and overweight) among postmenopausal women using BMI, WHtR and WHR. Education and ethnicity are predictors of excess weight. Contribution: The study's findings can be used to develop interventions that focus on addressing excess weight in postmenopausal women within the Ghanaian context.